Prime Online: Exploring Teacher Professional Development for Creating Inclusive Elementary Mathematics Classrooms. (May 2018) - Griffin, Cynthia C.; Dana, Nancy F.; Pape, Stephen J.; Algina, James; Bae, Jungah; Prosser, Sherri K.; League, Martha B.
Enhancing all students' academic performance continues to be a national priority, and although achievement gains have been made overtime, shortfalls in mathematics learning for students with disabilities (SWD) remain. Research reveals that a substantial portion of the variability in students' mathematics achievement gains is due to the teacher. To address the need for teacher professional development (PD) in mathematics for SWD and other struggling mathematics learners, we designed and studied Prime Online —a yearlong, online, PD program with support from an Institute of Education Sciences (IES) Goal 2 Development and Innovation research grant. In this article, the development process and an exploratory study are discussed. Study findings suggest that Prime Online positively influenced general and special education teachers' reported beliefs and practices, and their learning of mathematics content for teaching, and generated high teacher satisfaction ratings. No difference in the performance of SWD on a state accountability measure of mathematics was found. Implications for further research are discussed.